PENGEMBANGAN MEDIA FUN THINKERS UNTUK MENINGKATKAN LITERSI BERHITUNG SISWA KELAS II UPT SDN TINGKIS - Dea Elisiana; Iis Daniati Fatimah (Prodi PGSD Universitas PGRI Ronggolawe, 2024)
This research uses the type of research and development (R&D). By using the ADDIE (Analysis-Design-Develop-Implementation-Evaluation) model, this research aims to develop Fun Thinkers media to increase the numeracy literacy of class II UPT SDN Tingkis students. The data collection instruments used are observation sheets, interviews, media, material and language validation sheets, teacher and student response questionnaire sheets, and student test widths. The data analysis techniques used are observation and interview data, validity data analysis, practicality data analysis, and effectiveness data analysis. This research resulted in validation results from media experts of 83.15%, material experts of 94%, language experts of 88.89%, so the validity assessment criteria have the